Development of Android Based Interactive Learning Media Using Articulate Storyline 3 to Improve Motivation and Conceptual Understanding in Informatics Lessons - Silfia Hasanah; Munir Munir; Wahyudin Wahyudin; Galih Yudha Saputra (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study aimed to develop Android-based interactive learning media using the Articulate Storyline 3 application for teaching computer hardware in Grade VII Informatics classes. The development model used was ADDIE, involving expert validation and effectiveness testing in both experimental and control classes. Validation results indicated the media was highly feasible, with average Likert-scale scores above 4.4. Effectiveness testing showed a significant improvement in studentsâ€™ conceptual understanding and learning motivation in the experimental class, with an N-Gain score of 0.77 (high category) and motivation levels increasing from â€œHighâ€ to â€œVery High.â€ These findings support the integration of Android-based technology in education as an effective strategy to improve learning outcomes, especially in abstract and technical subjects.